Strategi Kepemimpinan Kepala Madrasah Meningkatkan Kinerja Guru Melalui Nilai Kayuh Baimbai - Asysyddiqi, Hamdan Ikrimah; Madihah, Husnul; Rahmi, Agustina (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
The purpose of the study was to analyze and find out the leadership strategy of the madrasa head in improving teacher performance through the value of kayuh baimbai at the Datu Aling madrasa in Tapin district. Qualitative research methods with a case study approach, data collection techniques using observation, interviews, and documentation studies. The sources of data were the madrasah head, teachers, foundation leaders, madrasah committee, and student guardians. Data analysis uses the flow of collection, reduction, presentation of data and conclusion drawing. The results of the study revealed that: 1) Madrasah head leadership strategies include: program planning. Implementation, supervision and evaluation of programs that involve all parties, 2) teacher performance has gone well, as evidenced by the activeness of teachers in every learning activity and the absence of the term empty hours in madrasas. As well as being realized in the form of several madrasah achievements both academic and non-academic. 3) The efforts of the Madrasah Principal in improving teacher performance through the value of kayuh baimbai have been realized by providing relevant training and direction from the head of the Foundation and madrasah head to teachers and fostering a sense of mutual cooperation and cooperation in every activity program implementation to realize good quality education according to education standards.